Impact of COVID-19 on Recovered Athletes Returning to Competitive Play in the NBA "Bubble". Issue 3 (23rd March 2021) - Vaudreuil, Nicholas J.; Kennedy, Amy J.; Lombardo, Stephen J.; Kharrazi, F. Daniel
Background: The global pandemic caused by COVID-19 has had far-reaching implications for the world of professional sports. The National Basketball Association (NBA) suspended active regular season play in 2020 after a player tested positive for SARS-CoV-2. No previous studies have examined the impact of COVID-19 on return to play in the NBA. Purpose/Hypothesis: The purpose of this study was to examine performance measures for NBA players who had recovered from COVID-19 and returned to play in the NBA bubble. We hypothesized that these athletes would play fewer minutes and have decreased performance statistics compared with performance during the 2019-2020 regular season prior to the lockdown and with career averages. Study Design: Case series; Level of evidence, 4. Methods: NBA players positive for SARS-CoV-2 who played in both the 2019-2020 regular season and the NBA bubble were identified. Data collected included player demographics and player performance statistics. Results: A total of 20 players were included in the study. Players who had recovered from COVID-19 played significantly fewer minutes per game in the NBA bubble (25.8 vs 28.7; P = .04) and made fewer field goals per game (4.6 vs 5.4; P = .02) compared with the season prior to shutdown. While NBA bubble players demonstrated slight decreases in averages for points ( P = .06), rebounds ( P =.13), assists ( P = .23), steals ( P = .30), and blocks ( P = .71) per game, these were not statistically significant. Aside from an increase in made free throws per game during the bubble (3.3 vs 2.8; P = .04), player performance was not significantly different from career averages. Conclusion: For players who tested positive for SARS-CoV-2 prior to playing in the NBA bubble, the current study demonstrated that despite playing significantly fewer minutes per game, performance was not statistically different from either their pre-COVID 2019-2020 level of play or from their career averages.